Examining the relationship between macroeconomic variables and stock prices. Evidence from the Ghana stock exchange - BAFFOUR, STEPHEN GYAU (2016)
A Thesis Submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the degree of Master of Business Administration Finance,